Examining the relationship between perceived teacher support and students’ academic engagement in foreign language learning: Enjoyment and boredom as mediators - Zhao, Yanlin; Yang, Lianrui (Frontiers in Psychology, 2022)
As an important contextual factor influencing various aspects of students’ learning, teacher support has been widely explored in general education but largely overlooked in the English as a Foreign Language (EFL) context. Given its potential positive role in students’ academic performance, the present study intended to investigate the relationship between perceived teacher support, enjoyment, boredom, and academic engagement in the EFL context. In so doing, 1094 Chinese high school students were recruited to complete the online questionnaire of the four variables. SPSS and PROCESS macro were used for descriptive, correlational, and mediation analyses. The results showed that students had moderate levels of perceived teacher support, enjoyment, and academic engagement and a low level of boredom. Further correlation analyses indicated medium to large correlations between perceived teacher support, enjoyment, boredom, and academic engagement. Enjoyment and boredom collectively mediated the relationship between perceived teacher support and academic engagement. Directions for future research and implications for researchers and educators are presented at the end.